Spatio Temporal Analysis of Urban Heat Stress Using Multispectral Data - Antomi, Yudi (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
The effect of urbanization on the future atmospheric environment of cities around the world remains uncertain in the context of climate change. Using temperature measures can be analyzed how changes in the thermal environment can affect human well-being. The study aims to support city planning authorities in the study of urban heat stress hazards. Therefore, land surface temperatures (LST), as well as Physiological Equivalent Temperature (PET), are applied to take into account the spatial distribution of heat stress. Heat stress conditions are mapped and generated by connecting land surface temperatures with PET values. Landsat 7 ETM+ and Landsat 8 OLI/TIRS remote sensing data are used to capture LST, and PET categories are used to assess heat stress based on LST. Based on the results of the spatial analysis shows there is an increase in the hazard of spatiotemporal heat stress in Padang city, in the year 2007 the highest LST reached 300C in the category of Moderate Heat Stress with an area of 1.2 hectares, but in the year 2017, the highest temperature reached 330C with a wide area of Moderate Heat Stress reaching 730.98 hectares. These results demonstrate the need for mitigating heat stress through the city's green open spaces.